The Sharia Capital Market System In Indonesia - Dwiatmaja, Ahmad Zikri; Mustamin; Rahmawati Muin (Indonesian Scientific Publication, 2024)
Currently, the development of the Sharia capital market in Indonesia encounters several fundamental issues. The primary challenge is the lack of understanding and knowledge among Indonesians regarding investments in Sharia-based capital markets. Additionally, there is an absence of adequate regulations to support Sharia investments within the Indonesian capital market, and there is a perception that investing in Sharia capital markets involves higher costs compared to other financial sectors. This article employs a library research method, utilizing resources such as books, journals, documents, and previous research reports available in libraries. The study concludes that the Sharia capital market holds substantial potential for sustainable economic growth. Although many challenges persist, concrete measures to improve regulatory clarity, support product innovation, and raise public awareness can help strengthen the Sharia capital market globally. Comprehensive understanding and strong support from governments and regulators are essential to maximize the economic and financial benefits of Sharia capital markets.